Zur Dynamik von Qualifizierung und Karriere in Japan - Ernst, Angelika [Verfasser] (My University, 1997)
The personnel management of Japanese employers is based on strong incentives for continuous learning. As far as core personnel ist concerned less importance than in German firms is given to specified levels of qualification. Instead, the stress is put on the dynamics of improvement of knowledge, on the readiness of employees to add new knowledge, and on the development of management qualifications. Effort and achievement in learning and re-learning is rewarded with steady promotion in the firm's hierachy. The main merits of the concept are high flexibility of firms and strong motivation of employees. On the other hand, this mechanism has resulted in very high ratios of middle level managers, in disadvantages for specialists and for persons changing their employer, and in the discrimination of women. ( DIPF/Orig.)
Keywords: S 1 Stufen der Berufsbildung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; G 1.2.3.1 Potenziale; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; S 5 Organisationsentwicklung; G 2 Trends & Entwicklungen; I 2.2 Europa; I 2.3 Außereuropäische Regionen; I 2.3.4 Asien; Berufsverlauf; Bildungssystem; Berufstätigkeit; Lebenslanges Lernen; Qualifikation; Qualifizierung; Berufsausbildung; Arbeitsmarkt; Personalpolitik; Auslese; Fachkompetenz; Leistungsfähigkeit; Führungskraft; Management; Reform; Empirische Untersuchung; Analyse; Ausland; Japan